Electronic, optical and thermoelectric properties of PrMO3 (M = Al, Ga, In) from first-principles calculations. Issue 65 (23rd June 2016) - Sakhya, Anup Pradhan; Rai, D. P.; Sandeep; Dutta, Alo; Thapa, R. K.; Sinha, T. P.
Abstract : Though PrInO3 is structurally anisotropic it is found to be optically isotropic which is the basic requirement for ceramic scintillators. Abstract : We have systematically investigated the electronic structure, optical properties, Born effective charges and the thermoelectric properties of PrMO3 (M = Al, Ga, In) compounds using first-principles density functional theory calculations. Two different density functional approaches, the full potential linearized augmented plane wave method (FP-LAPW) and the plane wave pseudo potential method were used for the present study. A direct band gap at a Γ point of 3.8 eV, 3.07 eV and 2.9 eV is observed for PrAlO3 (PAO), PrGaO3 (PGO) and PrInO3 (PIO). The optical anisotropy of PAO and PGO is revealed from the computed optical properties such as complex dielectric function, refractive index, and absorption coefficient whereas PIO is found to be optically isotropic in the low energy range making it suitable for use in the development of ceramic scintillators. The inter-band transitions to the optical properties are analyzed with the help of calculated band structures. The Born effective charge and the static dielectric tensor of these materials have also been calculated.